(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines the role of organizational agility in improving institutional performance within the General Administration of the General Electricity Company of Libya. It addresses challenges arsin from the electricity sector, the scale and vertical integration of operations, and the need to increase responsiveness without weakening safety, governance, or accountability. The study adopts a descriptive-analytical approach within an applied documentary case-study design. Peer-reviewed research and official documents concerning the company and Libya’s electricity sector were analyzed. The evidence was organized through a qualitative matrix linking organizational challenges, agility dimensions, proposed interventions, and performance indicators. The analysis covers five dimensions: sensing agility, decision-making agility, operational flexibility, learning and empowerment, and digital agility. The findings indicate that institutional performance can be strengthened by integrating information, shortening decision cycles, clarifying authority and escalation paths, forming cross-functional teams, documenting lessons learned, and aligning digital transformation with process redesign and data-quality improvement. Agility is not interpreted as bypassing institutional controls, but as redesigning them to balance responsiveness, decision quality, and risk management. The study proposes a phased framework that begins with mapping data and decision flows and establishing baseline indicators, proceeds through pilot projects in maintenance, outage management, and customer service, expands through systems integration and enterprise dashboards, and concludes with institutionalized governance, learning, and continuous improvement. It also identifies indicators covering decision time, fault response and service restoration, critical-asset availability, planned maintenance, inventory-data accuracy, complaint closure, beneficiary satisfaction, and corrective-action completion. These measures assess agile practices without reducing performance to speed or cost alone. The study contributes an actionable diagnostic model, implementation roadmap, and balanced indicator set for empirical testing. It concludes that organizational agility can improve reliability, efficiency, service quality, and institutional sustainability when supported by senior leadership, gradual implementation, employee participation, reliable data, and field research to statistically test the proposed relationships.